Fe-55 scintillation resin and preparation method and application thereof

By developing FE-55's flashing resin, the problem of lack of sensitivity to the production and detection of organic radioactive waste liquid in existing liquid flash detection technology has been solved, and high-sensitivity FE-55 detection and environmental detection process is achieved.

CN119350532AActive Publication Date: 2025-01-24LANZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411907486.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-01-24
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The existing liquid scintillation detection technology produces a large amount of organic radioactive waste liquid when detecting radionuclides, and the detection sensitivity is insufficient.

Method used

Develop a Fe-55 scintillation resin, prepared through the polymerization reaction of polymerized monomers, scintillator, wave-shifting agent, extraction agent, dispersant, initiator, organic solvent and water, for liquid scintillation measurement. The resin features high detection sensitivity and easy separation.

Benefits of technology

A high-sensitivity detection of Fe-55 is achieved, and the generation of organic radioactive waste liquid is avoided, and the resin can be separated by simply filtering, which has good stability and repetitive utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350532A_ABST
    Figure CN119350532A_ABST
Patent Text Reader

Abstract

The invention provides Fe-55 scintillation resin as well as a preparation method and application thereof, and belongs to the technical field of separation and detection. The Fe-55 scintillation resin provided by the invention is obtained by polymerization reaction of a polymeric monomer, a scintillating agent, a wave shifting agent, an extracting agent, a dispersing agent, an initiator, an organic solvent and water, and the scintillating agent can convert received alpha or beta ray energy into fluorescence; the wave shifting agent transfers energy released by the scintillation group to a proper wavelength range of the photomultiplier to reduce the self-absorption effect, and the extraction agent can generate specific interaction with 55Fe, so that the resin has excellent adsorption effect and detection effect on 55Fe, has relatively good detection accuracy and stability, and can be used for detecting the 55Fe after separation or detection is completed. And separation can be realized through simple filtration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of separation and detection technology, specifically relating to a Fe-55 scintillation resin, its preparation method, and its application. Background Technology

[0002] The decommissioning of nuclear facilities marks the end of their life cycle. It is a key link in the full life cycle management of nuclear facilities and an important measure for environmental protection. Its core goal is to safely handle and dispose of radioactive materials and transform the nuclear facility site into an unrestricted open green space or for other purposes. In the context of nuclear facility decommissioning, accurate analysis and assessment of the concentration level of radionuclides is crucial and has great significance for environmental protection and human health. Among the many radionuclides, 55 Fe, due to its long half-life and decay via K capture, emits soft X-rays, making it an important research subject in the context of nuclear facility decommissioning.

[0003] Current technologies primarily detect radionuclides through liquid scintillation, which involves preparing a scintillation agent with solvents and additives to create a liquid scintillation solution for detection. However, this method generates a large amount of organic radioactive waste liquid, which has always been a technical challenge for liquid scintillation measurement technology, and its detection sensitivity still needs improvement. Summary of the Invention

[0004] The purpose of this invention is to provide a Fe-55 scintillation resin, its preparation method, and its applications. The Fe-55 scintillation resin provided by this invention can be used for liquid scintillation measurement, is easy to separate, and has high detection sensitivity.

[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution: The present invention provides a scintillation resin of Fe-55, which is obtained by polymerization reaction comprising a polymerizing monomer, a scintillation agent, a wave-shifting agent, an extractant, a dispersant, an initiator, an organic solvent and water; wherein the extractant comprises at least one selected from bis(2,4,4-trimethylpentyl)phosphonic acid, 2-ethylhexyl phosphate mono-2-ethylhexyl ester and di(2-ethylhexyl) phosphate.

[0006] Preferably, the scintillator comprises at least one of 2,5-diphenyloxazole and p-terphenyl.

[0007] Preferably, the wave-shifting agent comprises at least one of 1,4-bis-(2-(5-phenyloxazolyl))benzene and diphenylmethane.

[0008] The present invention also provides a method for preparing the Fe-55 scintillation resin described in the above technical solution, comprising the following steps: (1) Mix water and dispersant to obtain an aqueous phase; (2) The polymer monomer, scintillator, wave-shifting agent, initiator, extractant and organic solvent are mixed to obtain an organic phase; (3) The aqueous phase obtained in step (1) and the organic phase obtained in step (2) are mixed and polymerized to obtain Fe-55 scintillation resin; The steps (1) and (2) are not in any particular order.

[0009] Preferably, the dispersant in step (1) includes at least one of polyvinyl alcohol, gelatin and calcium chloride.

[0010] Preferably, in step (1), the mass ratio of the dispersant to the volume of water is (0.4~1) g: (200~250) mL.

[0011] Preferably, the polymerizing monomers in step (2) include styrene and divinylbenzene.

[0012] Preferably, in step (2), the mass ratio of styrene, divinylbenzene, scintillator, wave-shifting agent, initiator and extractant is (12~14):(2~4):(0.03~0.6):(0.005~0.1):(0.2~0.4):(2~4).

[0013] Preferably, the polymerization temperature in step (3) is 60~70℃ and the polymerization time is 5~6h.

[0014] This invention also provides the Fe-55 scintillation resin described in the above technical solution, or the Fe-55 scintillation resin prepared according to the preparation method described in the above technical solution. 55 Applications in Fe separation and detection.

[0015] This invention provides a Fe-55 scintillation resin, obtained by polymerization of a polymerizing monomer, a scintillator, a wave-shifting agent, an extractant, a dispersant, an initiator, an organic solvent, and water. The extractant comprises at least one selected from bis(2,4,4-trimethylpentyl)phosphonic acid, 2-ethylhexyl phosphate mono-2-ethylhexyl ester, and di(2-ethylhexyl) phosphate. The scintillator in the scintillation resin provided by this invention can convert received α or β ray energy into fluorescence, while the wave-shifting agent transfers the energy released by the scintillator groups to a suitable wavelength range for the photomultiplier tube, reducing self-absorption effects. The extractant can interact with… 55 Fe undergoes specific interactions, thereby enabling the resin to... 55Fe has excellent adsorption and detection properties, resulting in good detection accuracy and stability. After separation or detection, it can be separated by simple filtration. The results of the examples show that the detection limit of the Fe-55 scintillation resin provided by the present invention is 0.11 Bq, and the detection efficiency after multiple measurements is consistently above 5%. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 SEM image of the resin prepared in Comparative Example 1. Figure 2 SEM image of the Fe-55 scintillation resin prepared in Example 1; Figure 3 Infrared spectra of the resins prepared in Comparative Example 1 and Example 1; Figure 4 The scintillation resin for Fe-55 prepared in Example 1 adsorbed 16 mg / g of Fe. 3+ The subsequent fluorescence spectrum; Figure 5 The amount of iron ions adsorbed by the Fe-55 scintillation resin prepared in Example 1 under different solid-liquid ratio conditions; Figure 6 The amount of iron ions adsorbed by the Fe-55 scintillation resin prepared in Example 1 under different pH conditions; Figure 7 The adsorption rate of iron ions by the Fe-55 scintillation resin prepared in Example 1 at different times; Figure 8 Comparison of the adsorption capacity of iron ions by the scintillation resins of Fe-55 prepared in Examples 1-4; Figure 9 Three batches of Fe-55 scintillation resin prepared according to the preparation method of Example 1 were used to prepare the scintillation resin. 55 Results of liquid scintillation test of Fe; Figure 10 The Fe-55 scintillation resin prepared in Example 1 showed effects on scintillation at 1d, 5d, 10d, and 20d. 55 Results of liquid scintillation test for Fe. DETAILED DESCRIPTION

[0017] This invention provides a scintillation resin of Fe-55, which is obtained by polymerization reaction comprising a polymer monomer, a scintillation agent, a wave-shifting agent, an extractant, a dispersant, an initiator, an organic solvent and water.

[0018] In the present invention, the scintillator preferably includes at least one of 2,5-diphenyloxazole and p-terphenyl, more preferably 2,5-diphenyloxazole (PPO). In the present invention, the scintillator can convert received α or β ray energy into fluorescence.

[0019] In this invention, the wave-shifting agent preferably comprises at least one of 1,4-di-(2-(5-phenyloxazolyl))benzene and diphenylmethane, more preferably 1,4-di-(2-(5-phenyloxazolyl))benzene (POPOP). In this invention, the wave-shifting agent transfers the energy released by the scintillation group to a suitable wavelength range for the photomultiplier tube, reducing the self-absorption effect.

[0020] In this invention, the extractant comprises at least one selected from bis(2,4,4-trimethylpentyl)phosphonic acid, 2-ethylhexyl phosphate mono-2-ethylhexyl ester, and di(2-ethylhexyl) phosphate, preferably bis(2,4,4-trimethylpentyl)phosphonic acid (Cyanex 272). In this invention, the extractant is capable of reacting with… 55 Fe undergoes specific interactions, thereby improving detection sensitivity.

[0021] The scintillator in the scintillator resin provided by this invention can convert the received α or β ray energy into fluorescence, while the wave-shifting agent transfers the energy released by the scintillator group to a suitable wavelength range for the photomultiplier tube, reducing the self-absorption effect. The extractant can interact with... 55 Fe undergoes specific interactions, thereby enabling the resin to... 55 Fe has excellent adsorption and detection effects, resulting in good detection accuracy and stability. As a solid material, it can be separated by simple filtration after separation or detection, without generating a large amount of organic radioactive waste liquid, making it greener and more environmentally friendly, reducing harm to the environment. The scintillation resin after detection can be recycled and reused, and can be used for continuous monitoring of radionuclides in complex environments.

[0022] The present invention also provides a method for preparing the Fe-55 scintillation resin described in the above technical solution, comprising the following steps: (1) Mix water and dispersant to obtain an aqueous phase; (2) The polymer monomer, scintillator, wave-shifting agent, initiator, extractant and organic solvent are mixed to obtain an organic phase; (3) The aqueous phase obtained in step (1) and the organic phase obtained in step (2) are mixed and polymerized to obtain Fe-55 scintillation resin; The steps (1) and (2) are not in any particular order.

[0023] Unless otherwise specified, the present invention does not impose any special restrictions on the source of the raw materials, and commercially available products well known to those skilled in the art can be used.

[0024] This invention mixes water and a dispersant to obtain an aqueous phase.

[0025] In this invention, the dispersant preferably includes at least one of polyvinyl alcohol (PVA), gelatin, and calcium chloride, more preferably polyvinyl alcohol (PVA). In an embodiment of this invention, the polyvinyl alcohol is polyvinyl alcohol 1788 type with an average molecular weight of 130.14.

[0026] In the present invention, the water is preferably deionized water.

[0027] In this invention, the preferred mass-to-volume ratio of the dispersant to water is (0.4~1) g : (200~250) mL. By controlling the mass-to-volume ratio of the dispersant to water within the above range, this invention ensures that the dispersant dissolves sufficiently.

[0028] In the present invention, the mixing temperature is preferably 50-70° C., more preferably 60° C. The present invention has no particular limitation on the mixing time, as long as the dispersant is fully dissolved in water.

[0029] The invention mixes polymerization monomers, scintillator, wave shifter, initiator, extractant and organic solvent to obtain an organic phase.

[0030] In the present invention, the polymerizable monomers preferably include styrene and divinylbenzene.

[0031] In the present invention, the initiator preferably includes at least one of azobisisobutyronitrile (AIBN) and dibenzoyl oxide. In the present invention, the initiator is used to initiate the polymerization reaction of the monomer.

[0032] In this invention, when the polymerizing monomers include styrene and divinylbenzene, the preferred mass ratio of styrene, divinylbenzene, scintillator, wave-shifting agent, initiator, and extractant is (12~14):(2~4):(0.03~0.6):(0.005~0.1):(0.2~0.4):(2~4). By controlling the mass ratio of each raw material within the above range, this invention can further improve the accuracy of detection.

[0033] In the present invention, the organic solvent preferably includes toluene, acetone or kerosene.

[0034] In this invention, the preferred mass ratio of styrene to organic solvent is 14:(2~20). By controlling the mass ratio of styrene to organic solvent within the above range, this invention ensures that all raw materials are fully dissolved.

[0035] The present invention does not have any special limitations on the mixing operation of the polymer monomer, scintillator, wave-shifting agent, initiator, extractant and organic solvent. The raw materials can be mixed evenly by means of material mixing techniques known to those skilled in the art.

[0036] After obtaining the aqueous phase and the organic phase, the present invention mixes the aqueous phase and the organic phase and carries out a polymerization reaction to obtain Fe-55 scintillation resin.

[0037] In this invention, the preferred mass ratio of the aqueous phase to the organic phase is (10~12):1. By controlling the ratio of the aqueous phase to the organic phase within the above range, this invention enables the polymerization product to be more fully dispersed and provides better detection sensitivity and accuracy.

[0038] The present invention does not have any special limitations on the mixing operation of the aqueous phase and the organic phase. The two phases can be mixed evenly by means of material mixing techniques known to those skilled in the art.

[0039] In this invention, the preferred temperature for the polymerization reaction is 60-70°C; the preferred reaction time is 5-6 hours; and the polymerization reaction is preferably carried out under stirring conditions. This invention does not impose any particular limitation on the stirring method or rate; stirring techniques well-known to those skilled in the art can be used. By controlling the temperature and time of the polymerization reaction within the above-mentioned ranges, this invention ensures that the polymerization reaction proceeds fully.

[0040] After the polymerization reaction is completed, the product of the polymerization reaction is preferably washed with water and dried in sequence to obtain Fe-55 scintillation resin.

[0041] The present invention does not impose any special limitations on the water washing operation; any water washing technical solution known to those skilled in the art can be used.

[0042] In this invention, the drying process is preferably freeze-drying. This invention does not impose any particular limitations on the freeze-drying operation; any technical solution well-known to those skilled in the art can be used.

[0043] This invention relates to a matrix obtained by crosslinking and polymerizing styrene and divinylbenzene, which is then modified with a scintillator, a wave-shifting agent, and an extractant, while controlling reaction parameters such as the amount of each component. The scintillator converts received α or β ray energy into fluorescence, while the wave-shifting agent transfers the energy released by the scintillator groups to a suitable wavelength range for the photomultiplier tube, reducing self-absorption effects. The extractant can interact with... 55 Fe undergoes specific interactions, thereby enabling the resin to... 55 Fe has excellent adsorption and detection effects, resulting in good detection accuracy and stability. Furthermore, after separation or detection, it can be separated by simple filtration.

[0044] This invention also provides the Fe-55 scintillation resin described in the above technical solution, or the Fe-55 scintillation resin prepared according to the preparation method described in the above technical solution. 55 Applications in Fe separation and detection.

[0045] The Fe-55 scintillation resin provided by this invention can be used for liquid scintillation measurement, enabling the measurement of... 55 Separation and detection of Fe.

[0046] The present invention does not impose any special limitations on the operation of the application, and any technical solution known to those skilled in the art can be used.

[0047] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the embodiments described are only some of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0048] Example 1 A method for preparing Fe-55 scintillation resin: (1) Water and polyvinyl alcohol (polyvinyl alcohol 1788 type, average molecular weight is 130.14) are mixed to obtain an aqueous phase, and the mass ratio of polyvinyl alcohol to water is 0.7g:250mL; (2) Styrene, divinylbenzene, scintillator 2,5-diphenyloxazole, wave-shifting agent 1,4-di-(2-(5-phenyloxazolyl))benzene, initiator azobisisobutyronitrile, extractant bis(2,4,4-trimethylpentyl)phosphonic acid and toluene were mixed to obtain an organic phase. The mass ratio of styrene, divinylbenzene, scintillator 2,5-diphenyloxazole, wave-shifting agent 1,4-di-(2-(5-phenyloxazolyl))benzene, initiator azobisisobutyronitrile and extractant bis(2,4,4-trimethylpentyl)phosphonic acid was 14:2:0.6:0.1:0.2:2, and the mass ratio of styrene to toluene was 14:2. (3) The aqueous phase obtained in step (1) and the organic phase obtained in step (2) are mixed (the mass ratio of the aqueous phase to the organic phase is 12:1), and the polymerization reaction is carried out at 60°C for 5 hours. The mixture is washed with water and freeze-dried to obtain the scintillation resin of Fe-55, which is denoted as PSresin.

[0049] Example 2 A method for preparing Fe-55 scintillation resin: (1) Water and polyvinyl alcohol (polyvinyl alcohol 1788 type, average molecular weight is 130.14) are mixed to obtain an aqueous phase, and the mass ratio of polyvinyl alcohol to water is 0.4g:250mL; (2) Styrene, divinylbenzene, scintillator 2,5-diphenyloxazole, wave shifter 1,4-bis-(2-(5-phenyloxazolyl))benzene, initiator azobisisobutyronitrile, extractant bis(2,4,4-trimethylpentyl)phosphonic acid and toluene were mixed to obtain an organic phase, wherein the mass ratio of styrene, divinylbenzene, scintillator 2,5-diphenyloxazole, wave shifter 1,4-bis-(2-(5-phenyloxazolyl))benzene, initiator azobisisobutyronitrile and extractant bis(2,4,4-trimethylpentyl)phosphonic acid was 14:2:0.6:0.1:0.2:2, and the mass ratio of styrene to toluene was 14:20; (3) The aqueous phase obtained in step (1) and the organic phase obtained in step (2) are mixed (the mass ratio of the aqueous phase to the organic phase is 12:1), and the polymerization reaction is carried out at 60°C for 5 hours. The mixture is washed with water and freeze-dried to obtain Fe-55 scintillation resin.

[0050] Example 3 A method for preparing Fe-55 scintillation resin: (1) Water and polyvinyl alcohol (polyvinyl alcohol 1788 type, average molecular weight is 130.14) are mixed to obtain an aqueous phase, and the mass ratio of polyvinyl alcohol to water is 1g:250mL. (2) Styrene, divinylbenzene, scintillator 2,5-diphenyloxazole, wave shifter 1,4-bis-(2-(5-phenyloxazolyl))benzene, initiator azobisisobutyronitrile, extractant bis(2,4,4-trimethylpentyl)phosphonic acid and toluene were mixed to obtain an organic phase, wherein the mass ratio of styrene, divinylbenzene, scintillator 2,5-diphenyloxazole, wave shifter 1,4-bis-(2-(5-phenyloxazolyl))benzene, initiator azobisisobutyronitrile and extractant bis(2,4,4-trimethylpentyl)phosphonic acid was 14:2:0.6:0.1:0.2:2, and the mass ratio of styrene to toluene was 14:15; (3) The aqueous phase obtained in step (1) and the organic phase obtained in step (2) are mixed (the mass ratio of the aqueous phase to the organic phase is 12:1), and the polymerization reaction is carried out at 60°C for 5 hours. The mixture is washed with water and freeze-dried to obtain Fe-55 scintillation resin.

[0051] Example 4 A method for preparing Fe-55 scintillation resin: (1) Water and polyvinyl alcohol (polyvinyl alcohol 1788 type, average molecular weight is 130.14) are mixed to obtain an aqueous phase, and the mass ratio of polyvinyl alcohol to water is 1g:250mL. (2) Styrene, divinylbenzene, scintillator 2,5-diphenyloxazole, wave-shifting agent 1,4-di-(2-(5-phenyloxazolyl))benzene, initiator azobisisobutyronitrile, extractant bis(2,4,4-trimethylpentyl)phosphonic acid and toluene were mixed to obtain an organic phase. The mass ratio of styrene, divinylbenzene, scintillator 2,5-diphenyloxazole, wave-shifting agent 1,4-di-(2-(5-phenyloxazolyl))benzene, initiator azobisisobutyronitrile and extractant bis(2,4,4-trimethylpentyl)phosphonic acid was 14:2:0.6:0.1:0.2:2, and the mass ratio of styrene to toluene was 14:5. (3) The aqueous phase obtained in step (1) and the organic phase obtained in step (2) are mixed (the mass ratio of the aqueous phase to the organic phase is 12:1), and the polymerization reaction is carried out at 60°C for 5 hours. The mixture is washed with water and freeze-dried to obtain Fe-55 scintillation resin.

[0052] Comparative Example 1 The extractant in Example 1 was omitted, and all other parameters were the same as in Example 1, resulting in scintillation resin microspheres, denoted as PSm.

[0053] The resins prepared in Comparative Example 1 and Example 1 were observed using scanning electron microscopy, and the obtained SEM images are shown below. Figures 1 and 2 As shown. Figures 1 and 2 As can be seen, the PSm microspheres exhibit a full shape and a smooth surface, indicating excellent physical properties and chemical stability. After introducing functional groups (extractants) into the surface of the microspheres, although the microspheres maintained their spherical shape, their surface became less smooth. This phenomenon may be due to changes in the chemical properties and physical structure of the resin surface caused by the introduction of functional groups. The introduction of functional groups may have increased the surface roughness. By comparing and analyzing the morphological differences between Comparative Example 1 and Example 1, it can be preliminarily inferred that the functional groups have been successfully introduced onto the microspheres, thereby achieving the extraction of Fe... 3+ The effective adsorption of Fe indicates that it has Fe 3+ Successful synthesis of resin with adsorption capacity.

[0054] The infrared spectra of the resins prepared in Comparative Example 1 and Example 1 are as follows: Figure 3 As shown. Figure 3 As can be seen, the infrared spectral characterization of PSm microspheres and PSresin revealed significant differences. Compared with PSm microspheres, PSresin showed significant differences at 2956 cm⁻¹. -1 A distinct absorption peak is observed at 1171 cm⁻¹, which corresponds to the CH stretching vibration in the alkyl chain of Cyanex 272. Furthermore, [the peak is also observed at 1171 cm⁻¹]. -1The absorption peaks are characteristic vibrational peaks of phosphonic acid groups, associated with the P=O stretching vibration in Cyanex 272. The presence of these characteristic peaks clearly confirms that functional groups have been successfully introduced into the microsphere surface.

[0055] The Fe-55 scintillation resin prepared in Example 1 adsorbed ferric ions, adsorbing 16 mg / g of Fe. 3+ The fluorescence spectrum of Fe-PSresin after the reaction is as follows: Figure 4 As shown. Figure 4 It can be seen that the adsorption of 16 mg / g of Fe 3+ The Fe-PSresin exhibited a significant fluorescence intensity peak at a wavelength of 416 nm, indicating that the material possesses high fluorescence emission efficiency at this specific wavelength. Since 416 nm falls within the optimal detection range of a photomultiplier tube (PMT), this suggests that the fluorescence properties of Fe-PSresin can be efficiently detected and applied.

[0056] Test Example 1 The Fe-55 scintillation resin prepared in Example 1 was mixed with a ferric salt (ferric nitrate) solution (ferric ion concentration of 50 ppm), and the pH was adjusted with nitric acid. Adsorption was performed for 24 h at a pH of 2 ± 0.05 and a temperature of 25 ± 0.5 °C. The adsorption amounts under different solid-liquid ratios are as follows: Figure 5 As shown. Figure 5 It can be seen from this that in Fe 3+ At a constant concentration, an increase in the solid-liquid ratio leads to an increase in the scintillation resin's effect on Fe. 3+ The adsorption capacity shows a decreasing trend until it reaches a steady state, at which point the adsorption capacity is at its minimum. Further increasing the solid-liquid ratio will not change the adsorption capacity. This phenomenon may be related to the saturation of adsorption sites; that is, under high solid-liquid ratio conditions, the active sites on the resin surface are fully utilized, leading to a stable adsorption capacity.

[0057] Test Example 2 5 mg and 10 mg of the Fe-55 scintillation resin prepared in Example 1 were mixed with a ferric salt (ferric nitrate) solution (ferric ion concentration of 50 ppm) at a solid-liquid ratio of 2.0 g / L. The pH values ​​were adjusted to 1, 2, and 3 with nitric acid, respectively. Adsorption was carried out at 25 ± 0.5 °C for 24 h. The adsorption amounts under different pH conditions are shown below. Figure 6 As shown. Figure 6 As can be seen from this, with the increase of pH, the resin's effect on Fe... 3+ The adsorption capacity gradually increases because the functional groups in the resin gradually deprotonate, which improves the resin's ability to adsorb Fe. 3+ The adsorption capacity of the resin is enhanced, and the electronegativity of the resin surface is increased, allowing the resin to interact with Fe. 3+The electrostatic interaction is enhanced, thereby promoting the electrostatic interaction of Fe. 3 + adsorption.

[0058] Test Example 3 The Fe-55 scintillation resin prepared in Example 1 was mixed with a ferric salt (ferric nitrate) solution (ferric ion concentration of 20 ppm) at a solid-liquid ratio of 2.0 g / L. The pH was adjusted to 2 ± 0.05 with nitric acid, and adsorption was carried out at 25 ± 0.5 °C. The adsorption rates at different adsorption times are shown below. Figure 7 As shown. Figure 7 As can be seen from this, the scintillation resin is effective against Fe. 3+ The adsorption of Fe reached 80% of its maximum at 200 min and essentially reached equilibrium after 4 h. In the initial stage of adsorption, the scintillation resin exhibited high adsorption efficiency for Fe... 3+ The adsorption capacity increases rapidly because the adsorbent provides a large number of adsorption sites and a high adsorption rate in the initial stage of adsorption. Subsequently, the scintillation resin... 3+ The adsorption rate decreases slightly because the number of adsorption sites available to the adsorbent gradually decreases as adsorption proceeds, and the Fe in the solution... 3+ The concentration gradually decreases, so the adsorption rate will decrease slightly, but adsorption equilibrium can be reached in 4 hours.

[0059] Test Example 4 The Fe-55 scintillation resins prepared in Examples 1-4 were mixed with a ferric salt solution (ferric ion concentration of 20 ppm) at a solid-liquid ratio of 2.0 g / L. The pH was adjusted to 2 ± 0.05 with nitric acid, and adsorption was carried out at 25 ± 0.5 °C for 24 h. The adsorption amounts of different examples are as follows. Figure 8 As shown, from Figure 8 As can be seen from Example 1, the scintillation resin prepared in Example 1 has the highest adsorption capacity for iron.

[0060] Application Example 1 1g of the Fe-55 scintillation resin prepared in Example 1 was placed in a plastic scintillation column, and 20mL of pH=2 was prepared. 55 Fe solution ( 55 Fe activity is 42.34 Bq) passed through this plastic scintillator column at a flow rate of 0.25 mL / min to achieve... 55 Effective adsorption of Fe, and then adsorbed 55 The Fe plastic scintillator column was transferred to a liquid scintillator bottle, while a scintillator containing equal volumes of Fe-55 scintillation resin and a plastic scintillator column, but without any Fe-55, was prepared. 55 A liquid scintillation bottle containing Fe solution was used as a blank sample. The blank sample and adsorbed Fe solution were analyzed using liquid scintillation spectrometry. 55The Fe-55 scintillation resin was scanned and analyzed, with a counting time of 60 min for each sample. The experimental data are shown in Table 1. The detection limit of the Fe-55 scintillation resin can be calculated to be 0.11 Bq based on the data in Table 1.

[0061] Table 1 Liquid scintillation test results

[0062] Three batches of Fe-55 scintillation resin were synthesized using the method in Example 1. Batch stability was tested, and background measurements were first performed on each batch. Subsequently, 40 Bq of nitric acid in 20 mL of pH=2 nitric acid system was added. 55 Fe activity was measured by passing it through three batches of resin, with a resin volume of 1 g and a flow rate of 0.25 mL / min. The results are as follows: Figure 9 As shown. Figure 9 As can be seen, the resin exhibits good batch stability.

[0063] Using the same method, the stability of the Fe-55 scintillation resin prepared in Example 1 was tested. The Fe-55 scintillation resin prepared in Example 1 was subjected to repeatability tests, with tests performed at 1 day, 5 days, 10 days, and 20 days, for a total of 4 tests. No post-processing was performed after each test. The experimental results are as follows: Figure 10 As shown. Figure 10 The calculated detection efficiencies are all above 5%.

[0064] In summary, the Fe-55 scintillation resin prepared by this invention has excellent stability and detection accuracy, avoiding the use of organic scintillation liquids and thus reducing the generation of radioactive organic waste liquids.

[0065] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A Fe-55 scintillating resin, characterized in that: The invention is obtained by polymerization reaction of a polymerizable monomer, a scintillator, a wave shifter, an extractant, a dispersant, an initiator, an organic solvent and water; the extractant comprises at least one of bis(2,4,4-trimethylpentyl)phosphonic acid, 2-ethylhexyl mono-2-ethylhexyl phosphate and di(2-ethylhexyl) phosphate.

2. The Fe-55 scintillating resin according to claim 1, characterized in that: The scintillator includes at least one of 2,5-diphenyloxazole and p-terphenyl.

3. The Fe-55 scintillating resin according to claim 1, characterized in that: The wave shifter includes at least one of 1,4-di-(2-(5-phenyloxazolyl))benzene and diphenylmethane.

4. The method for preparing a scintillation resin of Fe-55 according to any one of claims 1 to 3, comprising the following steps: (1) mixing water and a dispersant to obtain an aqueous phase; (2) mixing a polymerization monomer, a scintillator, a wave shifter, an initiator, an extractant and an organic solvent to obtain an organic phase; (3) mixing the aqueous phase obtained in step (1) and the organic phase obtained in step (2), and performing a polymerization reaction to obtain a Fe-55 scintillation resin; There is no chronological order for steps (1) and (2).

5. The preparation method according to claim 4, characterized in that: The dispersant in step (1) includes at least one of polyvinyl alcohol, gelatin and calcium chloride.

6. The preparation method according to claim 4, characterized in that: In the step (1), the mass ratio of the dispersant to the volume of water is (0.4-1) g: (200-250) mL.

7. The preparation method according to claim 4, characterized in that: The polymerizable monomers in step (2) include styrene and divinylbenzene.

8. The preparation method according to claim 7, characterized in that: In the step (2), the mass ratio of styrene, divinylbenzene, scintillator, wave shifter, initiator and extractant is (12-14): (2-4): (0.03-0.6): (0.005-0.1): (0.2-0.4): (2-4).

9. The preparation method according to claim 4, characterized in that: The polymerization reaction temperature in step (3) is 60-70° C., and the polymerization reaction time is 5-6 hours.

10. The scintillating resin of Fe-55 according to any one of claims 1 to 3 or the scintillating resin of Fe-55 prepared by the preparation method according to any one of claims 4 to 9. 55 Application in Fe separation and detection.

Citation Information

Patent Citations

  • Method for rapidly analyzing Fe-55 in water

    CN115356763A

  • Scintillation resin with dual functions of separating and detecting strontium-90 as well as preparation method and application of scintillation resin

    CN117024642A

  • Method for determining fe-55 and ni-63 in solid and liquid samples

    WO2009067975A1